Active Methodologies in Bilingual and Bicultural Education in the Course of Letters Libras of the Federal University of Ceará: perception of students - do Nascimento, Antonio Daley Marques; Marques, Cauê Jucá Ferreira; Munguba, Marilene Calderaro (Seven Editora, 2023)
The present study adopted the objective of describing the perception of students of the bachelor's degree course in Libras Letters of the Federal University of Ceará regarding the use of active methodologies in the mediation of bilingual and bicultural education. This is a Survey, a qualitative descriptive study, conducted from September 10 to 30, 2020, with 24 students. The inclusion criterion adopted the condition of having experienced the methodologies active in learning mediation in the period 2018.1 to 2019.2, in at least one of the five disciplines defined. The sampling of 24 respondents was intentional in the universe of 64 students who were distributed in 6 (25%) deaf and 18 (75%) listeners. A mixed digital questionnaire was applied through the Google Forms platform, containing 10 closed and 2 open questions, all in Portuguese and Libras, for each of the seven active methodologies techniques. The results point to the effectiveness of techniques in the teaching and learning process of bilingual classes, especially in the consolidation of student autonomy and the development of criticality. Research is suggested to evaluate, in the same way, the student's perception of the use of Active Methodologies as learning assessment strategies. DOI: https://doi.org/10.56238/methofocusinterv1-066